Differences among Three Measures of Reaction Time Based on Hand Laterality in Individual Sports - Badau, Dana; Baydil, Bilgehan; Badau, Adela (MDPI AG, 2018)
(1) Aim: The study aimed at assessing simple-reaction, recognition and cognitive-reaction times to visual stimuli among student athletes: boxing, gymnastics, taekwondo, judo, karate and wrestling, using computer games tests. (2) Methods: Our study involved 332 students and athletes. We applied three types of computer tests to measure the dominant and non-dominant hands: the simple motor reaction time through the Human Benchmark test, the recognition time by the Hit-the-dots and the cognitive reaction time by the Trail making test part B. (3) Results: For dominant and non-dominant hands, better results of individual sports were for: simply reaction time—boxing; recognition reaction time—taekwondo; cognitive reaction—judo. (4) Conclusions: Athletes had better simple reaction with the left hand than with the right hand. Athletes had better recognition and cognitive reaction time with the right hand than with the left hand regardless of the dominant hand. The outcomes of our study indicate that the reaction times of left and right hands were influenced by the hand laterality, the type of applied stimulus, the stress complexity of tests and the type of practiced sport.
Keywords: reaction time; visual stimulus; hand laterality; individual sports; computer games; Article; 4. Education